Muhu Holy Forest, Protected Area of Mahuze Clan as A Natural and Cultural Conservation - Trinovianto George Reinhard Hallatu,; I. D. Palittin, (Technium Social Sciences Journal, 2023)
Muhu Holy Forest is a protected area located in district Muting, Merauke. This holy forest belongs to the Mahuze clan, one of the large clans of the Marind tribe. The aim of this study was to describe the Holy Forest as one of the protected areas that serves to conserve nature and the culture of the Mahuze clan itself. This type of research is descriptive qualitative research with data collection methods are observation and interview. Observations were made by looking directly at the Holy Forest area, and interviews were conducted with several people with the name Mahuze and also customary elders of the Mahuze clan themselves. The results showed that the Holy Forest area contained various types of plants and animals. Some plants and animals in the Holy Forest are sago, rattan, coconut, bird of paradise, wild boar, and others. This Holy Forest is maintained by the Mahuze clan from various offers from both the government and the private sector for the development of oil palm plantations. The attitude of defending their area indirectly has preserved nature and also preserved the culture of their own ancestral heritag.